Rethinking preventive post‐discharge intervention programmes for very preterm infants and their parents. (March 2016) - van Wassenaer‐Leemhuis, Aleid G; Jeukens‐Visser, Martine; van Hus, Janeline W P; Meijssen, Dominique; Wolf, Marie‐Jeanne; Kok, Joke H; Nollet, Frans; Koldewijn, Karen
Abstract : Post‐discharge preventive intervention programmes with involvement of the parent may support the resilience and developmental outcomes of infants born very preterm. Randomized controlled trials of home‐based family‐centred intervention programmes in very preterm infants that aimed to improve cognitive outcome, at least at age two, were selected and updated on the basis of a recent systematic review to compare their content and effect over time to form the basis of a narrative review. Six programmes were included in this narrative review. Four of the six programmes led to improved child cognitive and/or motor development. Two programmes, which focused primarily on responsive parenting and development, demonstrated improved cognitive outcome up till 5 years after completion of the programme. The programmes that also focused on maternal anxiety remediation led to improved maternal mental well‐being, along with improved child behaviour, in one study – even at 3 years after completion of the programme. The magnitude of the effects was modest. Family‐centred preventive intervention programmes that aim at improvement of child development should be continued after discharge home to improve the preterm child's resilience. Programmes may be most effective when they support the evolvement of a responsive parent–infant relationship over time, as well as the parent's well‐being. What this paper adds: Responsive parenting is essential in post‐discharge interventions in preterm infants. Responsive parenting can improve cognitive, motor, and behavioural outcomes in preterm infants.